Hubungan Intensitas Menonton Youtube dengan Kemampuan Bicara dan Personal Sosial Anak Balita Usia (2–5 Tahun) di PAUDIT Insan Permata - Elza Tiara Ramadhan; Asmika; Farahdilla, Melany (Journal of Issues in Midwifery, 2023)
ABSTRACT Background: Based on Badan Pusat Statistik data (2020), 25,9% of gadget total users are children under 5 years old. Children tend to use gadgets to watch movies, music, video clips those on YouTube. Children under 5 years old who uses gadget have 3 times greater risk of experiencing language delays which can affect development in other aspects such as personal social. Aims: to find out the relationship between the intensity of watching YouTube with speaking and personal social skills in children (2-5 years old) at PAUD Islam Terpadu Insan Permata Malang. Method: analytical observational design applied with cross sectional approach and analyzed by using Spearman Corelation Rank method. Result: there was no meaningful relationship between the YouTube watching intensity and personal social skills, but there was a meaningful rrelationship between the YouTube watching intensity and speaking skills in children, ,p value= 0.029 < α=0.05 and correlation number of 0.345 which was included in moderat category. Conclusion: the YouTube watching intensity is related to speaking skills but unrelated to personal social skills in children (2-5 years old) at PAUD Islam Terpadu Insan Permata Malang. Key words: YouTube, Watching Intensity, Speaking Skills, Personal Social Skills, Children. ABSTRAK Latar Belakang: Data Badan Pusat Statistik tahun 2020 menyebutkan 25,9% dari total pengguna gadget diantaranya adalah balita. Anak-anak cenderung memakai gadget untuk menonton film, video klip, lagu seperti apa yang disediakan oleh aplikasi YouTube. Balita yang menggunakan gadget berisiko tiga kali lebih besar mengalami keterlambatan bahasa yang dapat memengaruhi perkembangan pada aspek lainnya seperti personal sosial. Tujuan Penelitian: untuk mengidentifikasi adanya korelasi antara intensitas menonton YouTube dengan kemampuan bicara dan personall sosial anak balita usia (2-5 tahun) dii PAUD IIslam Terpadu Insan Permata Malang.. Metode Penelitian: menerapkan desain observasionall analitik dengan pendekatan cross sectional dan diuji menggunakan metode Spearman Corelation Rank. Hasil Penelitian: tidak adanya hubungan antara iintensitas menonton YouTube dengan personal sosial anak. Namun, ada hubungan intensitas menonton YouTube dengan kemampuan bicara ditunjukkan oleh p value= 0.029. < α=.0.05 dan angka korelasi sebesar 0.345 termasuk kategori cukup (moderat). Kesimpulan: Intensitas menonton YouTube berhubungan dengan kemampuan bicara anak, namun tidak berhubungan dengan personal sosial anak. Kata kunci: YouTube, Intensitas Menonton, Kemampuan Bicara, Personal Sosial, Anak Balita.